Efectividad y aceptabilidad del entrenamiento en habilidades de la terapia dialéctica comportamental para familiares de personas con trastorno de personalidad límite - Navarro-Haro, María V.; Pérez-Hernández, Nuria; Serrat, Susana; Gasol-Colomina, Miquel (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Effectivity and acceptability of dialectical behavioral therapy skills training for family members of people with borderline personality disorder. Social and family environment is fundamental in the development and maintenance of Borderline Personality Disorder (BPD). Despite family members of people with BPD have more risk of suffering from psychological problems, there are not empirically-supported interventions for this population. Dialectical Behavior Therapy (DBT) has been adapted for families of people with BPD with encouraging results. The main goal of this study was to evaluate the effectiveness and acceptability of a 25-session intervention based on DBT in a sample of 7 family members of people with BPD and in a Spanish context. Pre-post treatment changes in the variables: emotional burden, depression, anxiety, difficulties in emotion regulation, and mindfulness skills, were measured. Preliminary results showed significant improvements in anxiety, emotion regulation and mindfulness and good implementation of the intervention. This study may benefit the implementation of family interventions for family members of people with BPD. Resumen: El ambiente social y familiar es fundamental en el desarrollo y mantenimiento del Trastorno Límite de la Personalidad (TLP). A pesar de que los familiares de personas con TLP tienen más riesgo de padecer problemas psicológicos, no existen intervenciones empíricamente validadas para esta población. La Terapia Dialéctica Comportamental (Dialectical Behavior Therapy, DBT) se ha adaptado para familiares de personas con TLP con resultados alentadores. El objetivo principal del estudio fue evaluar la efectividad y la aceptabilidad de una intervención de 25 sesiones basada en DBT en una muestra de 7 familiares de personas con TLP y en un contexto español. Se midieron los cambios pre-post tratamiento en las variables agotamiento emocional, depresión, ansiedad, desregulación emocional y atención plena. Los resultados mostraron mejoras significativas en ansiedad, regulación emocional y atención plena y una buena aceptación de la intervención. Este estudio podría favorecer la implantación de intervenciones para familiares de personas con TLP.